Economic policy strategies targeting the livestock sector. 2010-2015 (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2017)
The objective of this article is to analyze the sectorial impacts of the economic policy strategies directed to the livestock sector of Nicaragua. Thus, for the purposes of developing the research study, the analysis-synthesis method has been used to observe, understand, explain and assess the policy strategies implemented in the livestock sector of Nicaragua between 2010 and 2015. Hence, it is considered that these ordinances have been able to fulfill the objectives of growth of the sector and increase of its productivity. However, actions should be redirected to stimulate certain activities belonging to the sector such as porcine, which is not allocated sufficient resources for its development. At the same time, the high potential of this sector to contribute to the Sustainable Development Goals (SDG), due to their impact on food, economic and environmental systems, should be highlighted; however, this is being underutilized. Therefore, it is proposed to intervene in the challenges of livestock production and identify new tools and better policies for the development of sustainable livestock in the territory.
Keywords: Strategies; livestock; policies; growth; production